2005
DOI: 10.1103/physreve.71.051708
|View full text |Cite
|
Sign up to set email alerts
|

Surface anchoring and dynamics of jump-wise director reorientations in planar cholesteric layers

Abstract: A theoretical investigation is made into the dynamics of pitch jumps in cholesteric liquid-crystal layers having finite strength surface-anchoring conditions. A presentation is given of general formulations which connect the dynamics of pitch jumps with the key material parameters such as the viscosity, the specific form of the anchoring potential, and the dimensionless parameter Sd=K22/Wd, where K22 is the elastic modulus, W is the depth of the anchoring potential, and d is the layer thickness. To illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…As the temperature is changed, so-called pitch jumps occur which are easily observable as changes in the selective reflection wavelength. There have been several reports of thermal hysteresis in the pitch jumps [2][3][4], as well as theoretical treatments that relate the hysteresis to parameters including surface anchoring and cell thickness [5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…As the temperature is changed, so-called pitch jumps occur which are easily observable as changes in the selective reflection wavelength. There have been several reports of thermal hysteresis in the pitch jumps [2][3][4], as well as theoretical treatments that relate the hysteresis to parameters including surface anchoring and cell thickness [5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…Because the lasing frequency is determined by the edge mode frequencies there is an option for some variation of the lasing frequency inside the width of the dye line by changing the CLC pitch by means of the temperature variations [5,6] or by application to the layer of external electric or magnetic field [4]. Note, that some times smooth variations of the external agent may result in jump-like variations of the lasing Edge Modes in Chiral LC 227 frequency [19] connected with the jumps of the CLC pitch which are sensitive to the surface anchoring [20].…”
Section: Amplifying Lcmentioning
confidence: 97%
“…(19,20)). The mentioned relationship between the amplitudes of eigen and incident waves at the specific frequencies shows that the energy of radiation in CLC at the layer thickness for these frequencies is much higher than the corresponding energy of the incident wave at the same thickness.…”
Section: Nonabsorbing Lc Edge Modesmentioning
confidence: 97%
“…The physical motivation for the B form of surface energy is largely driven by pitch 'jumps' in cholesteric liquid crystals where the twist of the director is dominant and is related to the twist elastic constant K 2 [3][4][5]. By considering simple series expansions, it can be shown that the RP and B energies almost coincide when the actual surface twist angle is close to the easy direction / Ã .…”
Section: Introductionmentioning
confidence: 95%
“…if the director at the surface coincides with the easy direction. Recently, however, Belyakov et al [3][4][5] proposed an alternative form for a weak anchoring energy density that is particularly relevant to twist geometries. In our notation, this alternative version may be written as…”
Section: Introductionmentioning
confidence: 98%